High genetic diversity and limited spatial structure in an endangered, endemic South African sparid, the red steenbras Petrus rupestris. Issue 3 (1st October 2020) - Gouws, G; Kerwath, SE; Potts, WM; James, NC; Vine, NG; Cowley, PD
Abstract : The red steenbras Petrus rupestris is endemic to South Africa, occurring from False Bay in the Western Cape Province to St Lucia in the province of KwaZulu-Natal. This species, the largest member of the family Sparidae, has undergone a substantial stock decline as a result of overfishing and is considered to be collapsed. Various aspects of its life history, including high residency, predictable migrations, late maturity and longevity, have made it vulnerable to overexploitation. This study analysed the diversity and genetic structure of red steenbras across seven sampling regions, using mitochondrial (control region) and nuclear (S7 intron 1) DNA markers. Mitochondrial DNA haplotype diversity was high (0.976), exceeding that reported for most studied South African fishes. The haplotype network, a low global fixation index (φST = 0.013, p = 0.055) and pairwise comparisons indicated limited genetic differentiation among sampling regions and a general lack of spatial genetic structure, with the possible exception of the Agulhas Offshore and Transkei regions. Genetic diversity indices based on the S7 intron also indicated very low levels of genetic structuring among sampling regions. A Migrate-n analysis revealed highly asymmetrical migration rates and gene flow among the regions, reflecting aspects of the species' life history. These findings suggest that red steenbras exists as one panmictic population and should be managed as such.